Protein fractionation using ultrafiltration system for differents module configurations (2006)
Protein bioseparation is an important yet expensive activity especially in biotechnology industry. The production of protein is growth along with rapid commercialization and demand. Unfortunately, the industry having problem in term of cost and the production as the cost is extremely high but the production rate is low. The most effective way to solve this problem is by using membrane as the medium of separation. In this study, the effects for different mode of operations of ultrafiltration membranes – batch, single stage and two stages forward cascade. Amersham Quick Lab cross flow system was used to separate lysozyme by using 30 kDa polyethersulfone ultrafiltration membranes. For this research, the lysozyme is obtained from the cheapest source which is chicken egg white solution. Lysozyme is a very important protein in pharmaceutical field in order to produce a vaccine to prevent bacteria that inhabit the intestinal tract. In order to determine the most efficient configurations, the constant parameters are set for all configurations. The value of pH must be 10, the transmembrane pressure (TMP) is 1.0 bar, and the volume feed is 960 ml with the ratio of chicken egg white to sodium chloride 0.2 M is 1:31. The effective configuration can be determined by comparing the permeate flux, concentration of lysozyme in both permeate and retentate solution at 5 minutes after the separation process occurred and measurement of water flux. The analysis procedure is done using the UV-VIS spectrometer at wave length equal to 595 nm. The most effective configuration is two stages forward cascade which has the highest average permeate flux of 74.4 L/m2.h. Moreover, it also has percentage for concentration of lysozyme in permeate solution equal to 84% which is the biggest percentage of all configurations and the lowest value of water flux measurement after separation process compare to the benchmark value at TMP equal to 1.0 bar. The second configuration then is single stage and followed by batch at third place.